iLearning Model Approach in Creating Blockchain Based Higher Education Trust - Anwar, Aang Solahudin; Rahardja, Untung; Prawiyogi, Anggy Giri; Santoso, Nuke Puji Lestari; maulana, sabda (International Journal of Artificial Intelligence Research, 2022)
Today, higher education presents challenges in terms of educational and industrial collaboration. Both theoretical and practical, formal and informal are also part of the application of blockchain in education. Moreover, the assessment is still quite difficult to do to measure the skill level of students so that they can compete for jobs in the future With the problem of the academic curriculum that still uses writing media on paper, problems often arise regarding the validity of reliable document validation. So it is necessary to compare the knowledge obtained to match their abilities. From these problems, the goal was created to improve the higher education curriculum in order to find a revolutionary solution for document validation beliefs. Evaluation of the iLearning learning system combined with blockchain technology (ledger) has the benefit of being able to support these problems. By using Blockchain technology, a new learning model innovation is created in the form of the SCi-B (Student-Centered iLearning Blockchain) framework. SCi-B is a new innovation in the learning model where all activities use Blockchain so that its existence is able to manage and store all transactions, competencies, and teaching that can provide intensive assessments through digital certificates for the academic world and the world of work. So that SCi-B has a significant impact on the confidence in the results that have been obtained. This paper aims to answer the challenges of the world of education which is currently getting wider, more open, and everywhere. The model in the SCi-B framework of this paper can be used for all training institutions because this model can adapt to the specific professional needs of the job sector. This model has been validated by the existence of a web application whose use is very satisfying.